POSSIBILITIES FOR USING FOREIGN EXPERIENCE IN PRESCHOOL EDUCATION IN THE WORK OF EDUCATORS IN UZBEKISTAN - Bekimbetova Ainagul Amangeldievna; Artykbaeva Diana Polatovna (Scholar Express Journal, 2022)
The article "Possibilities of using foreign experience of preschool education in the work of educators of Uzbekistan" considers the possibility of using foreign experience in the development of the market of preschool education services in Uzbekistan. The analysis of the general indicators of the international preschool education market is given
Keywords: educational services market; pre-school education coverage level; early childhood education services; child